2010
DOI: 10.3109/02713680903521951
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Macular Pigment Following Supplementation with All Three Macular Carotenoids: An Exploratory Study

Abstract: Purpose: At the macula, the carotenoids meso-zeaxanthin (MZ), lutein (L), and zeaxanthin (Z) are collectively referred to as macular pigment (MP). This study was designed to measure serum and macular responses to a macular carotenoid formulation. Materials and Methods: Ten subjects were recruited into this study (five normal and five with early age-related macular degeneration [AMD]). Subjects were instructed to consume a formulation containing 7.3 mg of MZ, 3.7 mg of L, and 0.8 mg of Z everyday over an eight-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 47 publications
6
59
0
1
Order By: Relevance
“…142,143 Owing to the ability of macular pigments to serve as both effective absorbers of high-energy, short-wavelength light, as well as antioxidants, many investigators have started to measure macular pigment optical density. In fact, several groups of investigators have shown an increase in macular pigment density [144][145][146] Additionally, the lutein antioxidant supplementation trial (LAST) and the LUNA study both support the association between dietary supplementation and macular pigment density. 147,148 Others have noted great variability in macular pigment optical density depending on factors such as gender, body fat composition, and smoking.…”
Section: Variables In Photochemical Injurymentioning
confidence: 99%
“…142,143 Owing to the ability of macular pigments to serve as both effective absorbers of high-energy, short-wavelength light, as well as antioxidants, many investigators have started to measure macular pigment optical density. In fact, several groups of investigators have shown an increase in macular pigment density [144][145][146] Additionally, the lutein antioxidant supplementation trial (LAST) and the LUNA study both support the association between dietary supplementation and macular pigment density. 147,148 Others have noted great variability in macular pigment optical density depending on factors such as gender, body fat composition, and smoking.…”
Section: Variables In Photochemical Injurymentioning
confidence: 99%
“…Recently published trials have found that subjects supplemented with all the three macular carotenoids (MZ, L, and Z) exhibit significant increases in serum concentrations of these carotenoids and an associated augmentation in MP. 30,40 Indeed, a recent publication reports that the typical central peak of MP can be realised in subjects with atypical MP spatial profiles at baseline when supplemented with a preparation containing all the three macular carotenoids, but not with a supplement lacking MZ. 41 MZ in such supplements is derived from natural L, which has been extracted from the Aztec Marigold flower, and has been used to date in many clinical trials and subjected to toxicity studies.…”
Section: Safety Of Mzmentioning
confidence: 99%
“…41 MZ in such supplements is derived from natural L, which has been extracted from the Aztec Marigold flower, and has been used to date in many clinical trials and subjected to toxicity studies. 28,30,40 A recent study of supplemental MZ in human subjects has reported that renal and liver function, as well as lipid profile, haematological parameters, and markers of inflammation, are unaffected following supplementation with a formulation containing MZ, L, and Z. 30 MZ is also a component of a typical diet in countries and states where it is commonly used in hen feed to enhance the colouration of the egg yolk by the poultry industry (eg, Mexico), and no associated adverse events have ever been reported.…”
Section: Safety Of Mzmentioning
confidence: 99%
“…Meso-zeaxanthin in lutein supplements. 4. Additional evidence supporting lutein as the precursor of meso-zeaxanthin.…”
mentioning
confidence: 99%
“…We are very familiar with this method, as we have used it in several of our recently published studies. [3][4][5][6] In our review article, we point out the limitations of the standard 'two-step method' commonly used by many laboratories to quantify MZ. These limitations include the following: its labour intensive nature due to manual collection; operator dependency and potential for human error; and a very long sample run time, rendering it difficult to perform bulk analysis (eg, for clinical trials).…”
mentioning
confidence: 99%